2018
DOI: 10.1097/igc.0000000000001275
|View full text |Cite
|
Sign up to set email alerts
|

Gastric-Type Adenocarcinoma of the Uterine Cervix

Abstract: Gastric-type mucinous adenocarcinoma may have characteristic imaging features and poorer outcomes compared with UEA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Examples of characteristic magnetic resonance images are presented in Figure 1 [25]. Therefore, the radiologic features confirm the microscopic data, and included characteristics generally considered as contra-indications to fertility surgery in the common HPV-related type cervical cancer: large size, stromal invasion, involvement of the entire endocervix up to the internal os.…”
Section: Radiologic Featuresmentioning
confidence: 52%
“…Examples of characteristic magnetic resonance images are presented in Figure 1 [25]. Therefore, the radiologic features confirm the microscopic data, and included characteristics generally considered as contra-indications to fertility surgery in the common HPV-related type cervical cancer: large size, stromal invasion, involvement of the entire endocervix up to the internal os.…”
Section: Radiologic Featuresmentioning
confidence: 52%
“…Karamurzin et al (24) also reported that GMC exhibited significantly worse disease-specific survival than UEA. Similarly, Park et al (29) showed that GMC had a significantly shorter interval between surgery and disease recurrence (time to recurrence) compared to UEA. Overall, GMC exhibits aggressive behavior with significantly reduced survival compared to UEA, and GMC is thus considered a distinct entity from UEA.…”
Section: Discussionmentioning
confidence: 90%
“…The MRI manifestations of GAS are as follows: exogenous or endogenous mass, ill-defined margin, cysts within the tumor, and location in the upper cervical canal or the entire cervix. [7] And T1WI may show low signal intensity, while T2WI shows high signal intensity. In our patient, her abdominal and pelvic MRI showed that the signal intensity on T1WI was slightly low and on T2WI was slightly high of the uterine isthmus, with imaging diagnosis of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%